PERANCANGAN SISTEM INFORMASI GEOGRAFIS PELAYANAN PETA TEMATIK NILAI TANAH PADA KANTOR BADAN PERTANAHAN NASIONAL KOTA SERANG - Sutanto Sutanto; Widyawati Widyawati; Dodi Irawan (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
The rapid growth of large cities is heavily influenced by the complexity of the functions that run a city or region. Growth is very rapid development in large cities make the need for land and will further increase the value of land. Needs a very high soil have a tendency value of land in major cities increased. It is influenced by growing development in the region or the city. With the increase in land value that occurs is expected to be predicted so that the increase in land value that occurs not hampers the development of the area. While Geographic Information Systems (GIS) or also known as Geographic Information System (GIS), the end - the end is experienced significant development in line with advances in information technology. GIS is a computer-based information system that combines elements of the map (geographical) and information about the map (data attributes) that are designed to obtain, process, manipulate, analyze, demonstrate and display spatial data to complete the planning, process and investigate the problem. So they make a thematic map of land value that describes the amount of land value or the market price and the ground potential of a certain area, which serves as a spatial information (spatial) is Thematic Map Value of Land, as the information value of land in the city of Serang, making requires data of land prices based on market value.